RELATIONSHIPS AMONG READING ANXIETY, READING SELF-EFFICACY, AND READING COMPETENCY IN THE JUNIOR HIGH SCHOOL - Wiadnyana, I.P.E.C.; Tantra, D.K.; Saputra, I.N.P.H. (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
The general objective pursued is to describe and to relate the students’ reading anxiety, reading self-efficacy to their reading competency in the Junior High School in Singaraja. The design applied is a quantitative research. There were 96 students recruited using cluster quota sampling. The data were gathered using a reading anxiety scale, a reading self-efficacy scale, and an objective reading competency test. The obtained data were analyzed in two phases: descriptively and inferentially. The descriptions consisted of central tendency measures and dispersion. Whereas inferentially, the data were analyzed using pair-wise correlation and multiple correlation technique. The findings show that: 1) the students’ reading anxiety on higher-order-items is at high level while reading self-efficacy and reading competency on high-order-items are at the low levels; 2) the relations pair-wisely between the students’ reading anxiety and reading self-efficacy, students reading anxiety and reading competency on higher-order-items are negatively and significantly, while the students’ reading self-efficacy and reading competency on high-order-items are positively and significantly correlated; and 3) the simultaneous or multiple relationships of the reading anxiety and reading self-efficacy to the students’ reading competency is proven to be significant.Keywords: Correlation, Reading Anxiety, Competency, Self-efficacy